Marketing Communication: Concepts, Creative Strategy, Implementation - Agus Suhendra; M. Yusuf Sanny; Kamsariaty; Gratia Atanka Barus; Christophorus Indra Wahyu Putra (Green Publisher, 2024)
Abstract: Marketing communication articles: concepts, creative strategies and implementation within the scope of marketing management science. This article aims to create hypotheses regarding the relationship between factors, which can then be used for further research in the field of marketing management. The research method used in this research is descriptive qualitative. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results of this literature research include: 1) Concepts play a role in marketing communications; 2) Creative strategies play a role in marketing communications; and 3) Implementation plays a role in marketing communications.